2012
DOI: 10.1111/j.1365-2486.2012.02673.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate effects on size‐at‐age: growth in warming waters compensates for earlier maturity in an exploited marine fish

Abstract: Over the past 3 decades, North Sea Atlantic cod (Gadus morhua) have exhibited variable length‐at‐age along with declines in spawning stock biomass and timing of maturity. Multiple factors affecting growth and development in fish acted on this economically important stock over the same period including warming waters and an intensive fishery. Here, we employ North Sea cod as a model population, exploring how a physiologically relevant temperature metric (the growing degree‐day, GDD; °C day) can be used to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 82 publications
(148 reference statements)
2
37
0
1
Order By: Relevance
“…Among the potential sources of growth-independent plasticity examined, only temperature had a significant effect on female cod maturation; temperature experienced at age 0 had a significant negative effect on female cod L p50 at age 3, in agreement with earlier work (Wright et al 2011b, Neuheimer & Grønkjaer 2012. Previous findings for North Sea plaice and sole have also shown that elevated temperatures may accelerate maturation (Grift et al 2003, Mollet et al 2007).…”
Section: Temporal Trends In Pmrnssupporting
confidence: 80%
See 1 more Smart Citation
“…Among the potential sources of growth-independent plasticity examined, only temperature had a significant effect on female cod maturation; temperature experienced at age 0 had a significant negative effect on female cod L p50 at age 3, in agreement with earlier work (Wright et al 2011b, Neuheimer & Grønkjaer 2012. Previous findings for North Sea plaice and sole have also shown that elevated temperatures may accelerate maturation (Grift et al 2003, Mollet et al 2007).…”
Section: Temporal Trends In Pmrnssupporting
confidence: 80%
“…Since these environmental factors cannot explain the totality of the temporal trends in PRMNs, this suggests fisheries-induced evolution, in agreement with Neuheimer & Grønkjaer (2012) and Neuheimer & Taggart (2010) for haddock and Wright et al (2011b) for male cod. For female cod, the cohort effect was no longer significant after the inclusion of the environmental variables in the analysis, although it was significant before correction for multiple testing and it explained the largest part of the temporal change in PMRNs.…”
Section: Temporal Trends In Pmrnsmentioning
confidence: 77%
“…Warming temperatures are generally associated with faster growth rates (higher K) for temperate stocks (Thresher et al, 2007;Neuheimer & Grønkjaer, 2012). However, it has not been fully appreciated that, given the negative relationship between L ∞ and K, the downside of fast early growth is smaller adult body size.…”
Section: Age Intervalmentioning
confidence: 99%
“…When non-negative DD values are summed over some period of interest, the resultant cumulative degree-days at a given T o (CDD T o ;°C·days) is an index of the metabolically relevant thermal energy that was experienced over that period. This index is useful for describing concurrent patterns of growth and development (e.g., Neuheimer and Grønkjaer 2012;Venturelli et al 2010). Although DDs have been used for decades to describe growth and development in plants (e.g., Reaumur 1735, cited in Bonhomme 2000 and insects (e.g., Seamster 1950;Thorup 1963), this approach is rare in fish science, accounting for only 5% of all temperaturerelated growth studies between 1980 and 2006 (Neuheimer and Taggart 2007).…”
Section: Introductionmentioning
confidence: 99%